Maintenance of the southern Bay of Bengal cold pool. (September 2020) - Vinayachandran, P.N.; Das, Umasankar; Shankar, D.; Jahfer, S.; Behara, Ambica; Nair, T.M. Balakrishnan; Bhat, G.S.
Abstract: The region of relatively cooler water, sitting in the shadow zone of monsoon rainfall, around southern tip of India and around Sri Lanka, is known as the cold pool . A ship-board observations program to the east of Sri Lanka during the summer monsoon of 2009 captured two cooling events within the core of the Summer Monsoon Current (SMC). Time-series of temperature profiles within the cold pool showed a cooling of the sea surface temperature (SST) by about 0.3°C during 22–25 July 2009 and about 0.4°C during 29 July to 2 August 2009. During the cooling periods, both wind speed and mixed layer depth (MLD) increased, but the air-sea heat gain by the ocean remained positive. Efforts were made to estimate the temperature advection term by means of an Operation Advection strategy using CTD data at four locations about 6.5 km away from the time-series location and ship-board acoustic Doppler current profile measurements. Estimates of horizontal temperature advection suggest that these cooling events are induced by the advection of cooler water by the SMC. Simulation using an Indian Ocean model captures such cooling events and the model temperature equation shows that cooling events through the season are driven either by advection or by entrainment. Thus observations and model simulation concurrently demonstrate that cold pool is maintained through the summer monsoon by the SMC in spite of the ocean gaining heat from the atmosphere.